Imaging Artifacts of Liquid Embolic Agents on Conventional CT in an Experimental in Vitro Model - Schmitt, N.; Floca, R.O.; Paech, D.; El Shafie, R.A.; Seker, F.; Bendszus, M.; Möhlenbruch, M.A.; Vollherbst, D.F. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Endovascular embolization using liquid embolic agents is a safe and effective treatment option for AVMs and dural arteriovenous fistulas. The aim of this study was to assess the degree of artifact inducement by the most frequently used liquid embolic agents in conventional CT in an experimental in vitro model.MATERIALS AND METHODS: Dimethyl-sulfoxide–compatible tubes were filled with the following liquid embolic agents (n = 10, respectively): Onyx 18, all variants of Squid, PHIL 25%, PHIL LV, and n-BCA mixed with iodized oil. After inserting the tubes into a CT imaging phantom, we acquired images. Artifacts were graded quantitatively by the use of Hounsfield units in a donut-shaped ROI using a customized software application that was specifically designed for this study and were graded qualitatively using a 5-point scale.RESULTS: Quantitative and qualitative analyses revealed the most artifacts for Onyx 18 and the least artifacts for n-BCA, PHIL 25%, and PHIL LV. Squid caused more artifacts compared with PHIL, both for the low-viscosity and for the extra-low-viscosity versions (eg, quantitative analysis, Squid 18: mean ± SD, 30.3 ± 9.7 HU versus PHIL 25%: mean ± SD, 10.6 ± 0.8 HU; P < .001). Differences between the standard and low-density variants of Squid were observed only quantitatively for Squid 12. There were no statistical differences between the different concentrations of Squid and PHIL.CONCLUSIONS: In this systematic in vitro analysis investigating the most commonly used liquid embolic agents, relevant differences in CT imaging artifacts could be demonstrated. Ethylene-vinyl alcohol–based liquid embolic agents induced more artifacts compared with liquid embolic agents that use iodine as a radiopaque component.EVOHethylene-vinyl alcoholLDlow densityLEAliquid embolic agentLVlow viscosityMITKMedical Imaging Interaction Toolkitn-BCAn-butyl cyanoacrylate